Handbook of natural gas analysis - Speight, James G. (John Wiley & Sons, 2018)
A comprehensive resource to the origin, properties, and analysis of natural gas and its constituents Handbook of Natural Gas Analysis is a comprehensive guide that includes information on the origin and analysis of natural gas, the standard test methods, and procedures that help with the predictability of gas composition and behavior during gas cleaning operations and use. The author-a noted expert on the topic-also explores the properties and behavior of the various components of natural gas and gas condensate. All chapters are written as stand-alone chapters and they cover a wealth of topics including history and uses; origin and production; composition and properties; recovery, storage, and transportation; properties and analysis of gas stream and gas condensate. The text is designed to help with the identification of quality criteria appropriate analysis and testing that fall under the umbrella of ASTM International. ASTM is an organization that is recognized globally across borders, disciplines and industries and works to improve performance in manufacturing and materials and products. This important guide: -Contains detailed information on natural gas and its constituents -Offers an analysis of methane, gas hydrates, ethane, propane, butane, and gas condensate -Includes information on the behavior of natural gas to aid in the planning for recovery, storage, transportation, and use -Covers the test methods that are applicable to natural gas and its constituents -Written in accessible and easy-to-understand terms Written for scientists, engineers, analytical chemists who work with natural gas as well as other scientists and engineers in the industry, Handbook of Natural Gas Analysis offers a guide to the analysis, standard test methods, and procedures that aid in the predictability of gas composition and behavior during gas cleaning operations and use.